(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Basic Sciences Series, 2026)
Tobacco is one of the most important non-food crops in agriculture worldwide, where tobacco manufacturing processes generate large quantities of tobacco dust, which is rich in the compound nicotine, that can be extracted and utilized in various applications. In this study, three organic solvents of different polarities were used to extract nicotine from tobacco dust: ethanol (polar), ethyl acetate (medium polarity), and n-hexane (non-polar). The extraction process was carried out using a Soxhlet apparatus, and nicotine concentrations in the extracts were measured using high-performance liquid chromatography (HPLC) with a diode array detector (DAD SPD-M 20A). The results showed significant variation in nicotine concentrations among the extracts, with a concentration of 13.90 mg/g in the ethanol extract, 10.15 mg/g in the ethyl acetate extract, and 3.65 mg/g in the n-hexane extract. This variation is attributed to the polar nature of the nicotine molecule, which makes it more soluble in polar solvents in accordance with the "like dissolves like" principle. Based on the results, ethanol was found to be the most suitable solvent for extracting nicotine from tobacco dust due to its high efficiency, low toxicity, and acceptable cost.